PENGELOLAAN SISTEM SOSIAL MARGA DI SUMATERA SELATAN: Telaah atas Kontribusi Teori Fungsionalisme Struktural Parsons - Mohammad Syawaludin (Jurnal Sosiologi Reflektif, 2015)
Before colonial periode, community forms have been found in certain region to take traditions, Example owning selected self governance, arranging its rural citizen of law compiled. In referred such as Bali community, Banjar, in South Sumatra named as Marga, Minangkabau called Nagari. Countryside, Clan, Nagari, Marga or Kampong, often called as community and in which the right to manage region (sovereignty) which recognized customary right for land or region . It’s mean social custom communities have organization to arrange many aspects of governance, leadership structure, decision mechanism, and management of internal conflct.